The Prevalence of Hearing Impairment by Age and Gender in a Population-based Study - Alimohamad ASGHARI; Mohammad FARHADI; Ahmad DANESHI; Mehdi KHABAZKHOOB; Saman MOHAZZAB-TORABI; Maryam JALESSI; Hesamedin EMAMJOMEH (Iranian Journal of Public Health, 2017)
Background: This study aimed to determine the prevalence of hearing impairment (HI) by age and gender in a population aged 5 yr and older residing in Tehran, Iran.